The Dependence of CNT Aerogel Synthesis on Sulfur-driven Catalyst Nucleation Processes and a Critical Catalyst Particle Mass Concentration. Issue 1 (December 2017) - Hoecker, Christian; Smail, Fiona; Pick, Martin; Weller, Lee; Boies, Adam
Abstract The floating catalyst chemical vapor deposition (FC-CVD) process permits macro-scale assembly of nanoscale materials, enabling continuous production of carbon nanotube (CNT) aerogels. Despite the intensive research in the field, fundamental uncertainties remain regarding how catalyst particle dynamics within the system influence the CNT aerogel formation, thus limiting effective scale-up. While aerogel formation in FC-CVD reactors requires a catalyst (typically iron, Fe) and a promotor (typically sulfur, S), their synergistic roles are not fully understood. This paper presents a paradigm shift in the understanding of the role of S in the process with new experimental studies identifying that S lowers the nucleation barrier of the catalyst nanoparticles. Furthermore, CNT aerogel formation requires a critical threshold of Fex Cy  > 160 mg/m3, but is surprisingly independent of the initial catalyst diameter or number concentration. The robustness of the critical catalyst mass concentration principle is proved further by producing CNTs using alternative catalyst systems; Fe nanoparticles from a plasma spark generator and cobaltocene and nickelocene precursors. This finding provides evidence that low-cost and high throughput CNT aerogel routes may be achieved by decoupled and enhanced catalyst production and control, opening up new possibilities for large-scale CNT synthesis.